2020
DOI: 10.3389/fphys.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Rearrangements in the Maturation of Circulating Human Reticulocytes

Abstract: Red blood cells (RBCs) begin their circulatory life as reticulocytes (Retics) after their egress from the bone marrow where, as R1 Retics, they undergo significant rearrangements in their membrane and intracellular components, via autophagic, proteolytic, and vesicle-based mechanisms. Circulating, R2 Retics must complete this maturational process, which involves additional loss of significant amounts of membrane and selected membrane proteins. Little is known about the mechanism(s) at the basis of this termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 46 publications
2
15
1
Order By: Relevance
“…For instance, R1 reticulocytes undergo significant rearrangements in their membrane and intracellular components via several mechanisms including exosome release. Circulating R2 reticulocytes complete this maturational process, which involves additional loss of significant amounts of membrane and selected membrane proteins ( Minetti et al, 2018 , 2020 ). Membrane remodelling and vesicle formation also occur during RBC ageing ( Ciana et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, R1 reticulocytes undergo significant rearrangements in their membrane and intracellular components via several mechanisms including exosome release. Circulating R2 reticulocytes complete this maturational process, which involves additional loss of significant amounts of membrane and selected membrane proteins ( Minetti et al, 2018 , 2020 ). Membrane remodelling and vesicle formation also occur during RBC ageing ( Ciana et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the resistance to PS surface exposure has also been reported by Siegl et al (2013) in chorea-acanthocytosis after RBC stimulation with lysophosphatidic acid. Thus, pHypoÎČ has a high proportion of acanthocytes which could result from a maturation defect during the R1 reticulocyte stage known to undergo significant rearrangements in reticulocyte membrane and intracellular components via several mechanisms including exosome release and mitophagy (Minetti et al, 2018(Minetti et al, , 2020.…”
Section: Defective Rbc Maturation May Be a Novel Feature Of Heterozygmentioning
confidence: 99%
“…Accordingly, SDS-PAGE/western blotting evidenced that the α- and ÎČ-spectrin-to-Band3 ratios were not modified in pEl vs. healthy donors whereas the Band7-to-Band3 was decreased by ~30% (data not shown). Those data indicated that protein modifications in pEl did not result from the higher reticulocyte content since reticulocyte membranes instead show higher ÎČ-spectrin- and Band7-to-Band3 ratio as compared to mature RBCs [ 32 ]. The cytoskeleton:membrane occupancy was also preserved in pEl RBCs, in contrast to stored RBCs used as positive control, but its distribution was more heterogeneous ( Figure 2 A–C and Figure S3A ), showing spectrin gathering at one cell edge in ~75% of pEl RBCs vs. ~20% in pElm RBCs and ~5% in healthy RBCs (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatidylcholine and PS species, in particular those having long and unsaturated fatty acids, were strongly reduced as compared to a series of healthy donors ( Figure 4 E,G and Figure S8A–D ). Such lipid modifications were not due to the higher reticulocyte content in pEl since cholesterol and sphingomyelin have been shown to instead decrease and phosphatidylcholine and PS species to increase in reticulocytes vs. mature RBCs [ 32 ]. They could be related to the decreased content in very long chain fatty acid elongation protein 2 ( Figure S6B ), but also, in the case of PS, to the strong increase in several monoacyl lysoPS derivatives ( Figure 4 F,H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation